Ferroelectric Materials Synthesis and Characterization - Pelaiz Barranco, Aime (IntechOpen, 2015)
Ferroelectric materials receive great attention from the scientific international community because of the interesting phenomena they exhibit and their multiple applications such as transducers, capacitors, pyroelectric sensors, sonars, random access memories, etc. The demand for ferroelectric materials for technological applications enforced the in-depth research, in addition to the improvement of processing and characterization techniques. This book contains nine chapters and offers the results of several researches covering fabrication, properties, theoretical topics, and phenomena at the nanoscale.